Rapid black hole growth at the dawn of the Universe: a super-Eddington quasar at z = 6.6. Issue 2 (12th January 2019) - Tang, Ji-Jia; Goto, Tomotsugu; Ohyama, Youichi; Jin, Chichuan; Done, Chris; Lu, Ting-Yi; Hashimoto, Tetsuya; Kilerci Eser, Ece; Chiang, Chia-Ying; Kim, Seong Jin
Abstract: We present the analysis of a new near-infrared (NIR) spectrum of a recently discoveredz = 6.621 quasar PSO J006 + 39 in an attempt to explore the early growth of supermassive black holes (SMBHs). This NIR (rest-frame ultraviolet, UV) spectrum shows blue continuum slope and rich metal emission lines in addition to Lyα line. We utilize theMg II line width and the rest-frame luminosityL_3000 A to find the mass of SMBH ( M BH ) to be 10^8 M_, making this one of the lowest mass quasars at high redshift. The power-law slope index (αλ ) of the continuum emission is −2.94 ± 0.03, significantly bluer than the slope of αλ = −7/3 predicted from standard thin disc models. We fit the spectral energy distribution (SED) using a model which can fit local SMBHs, which includes warm and hot Comptonization powered by the accretion flow as well as an outer standard disc. The result shows that the very blue slope is probably produced by a small radial (∼230 gravitational radius, R g ) extent of the standard accretion disc. All plausible SED models require that the source is super-Eddington ( L bol / L Edd ≳ 9), so the apparently small disc may simply be the inner funnel of a puffed up flow, and clearly the SMBH in this quasar is in a rapid growth phase. We also utilize the rest-frame UV emission lines to probe the chemical abundance in the broad-line region (BLR) of this quasar. We find that this quasar has super solar metallicity through photoionization model calculations.